Microscopic mechanism of biphasic interface relaxation in lithium iron phosphate after delithiation - Shunsuke Kobayashi (Nature Portfolio, 2018)
Improving the performance of Li-ion batteries relies on understanding charging/discharging mechanisms. Here the authors visualize the interfacial structure and composition of a partially delithiated lithium iron phosphate single crystal as a function of time, revealing a mechanism of relaxation.